Eastern Christianity and late antique philosophy - Anagnostou-Laoutides, Evangelia ca. 20./21. Jh.; Parry, Kenneth (Texts and studies in Eastern Christianity, 2020)
"Readers of Eastern Christianity and Late Antique Philosophy will find a collection of authoritative papers from across the Neoplatonic and Eastern Christian traditions. It is only recently that scholars have started to take notice of the Eastern Christian engagement with late antique philosophical texts. This volume builds upon this new interest in order to show the dynamic nature of Neoplatonism and Eastern Christianity at a time when both faced a variety of challenges. The legacy of Greek philosophy in the Christian East fills the gap between the schools of Alexandria and Baghdad and brings into focus the intellectual history of the period. The aim of the volume is to stimulate interest in late antique philosophy and its reception in the Christian East"--